Effect of Plant Density on Yield and Forage Quality of Corn for Silage - Machinandiarena, Lorena (2013)
There is evidence that plant density of maize crops for silage affects herbage yield and quality (Cusicanqui and Lauer 1999). However, most of experimental information comes from trials with a range of plant densities between 20,000 and 140,000 plants per hectare (Pl/ha). This range would be insufficient to establish functional relationships between yield, forage quality, light interception and plant composition (Bertoia 1994). In addition, it is known that dry matter partitioning between plant components varies according to the environmental conditions of a given year (Andrade et al. 1991). The objective of this study was to determine the relationship between the light interception, yield, plant composition and herbage quality of corn for silage across a wide range of plant densities.